Translation Acceptability of Reduced Clause from English Into Indonesian in Google Translate - Syuqaira El Humaira; Violita Violita; Griselda Felicia (PRASASTI: Journal of Linguistics, 2024)
Google Translate is one of the online translation services that is simple and easy to use but has its own advantages and great impact in translating. The quality of Google Translate continues to be improved so that positive and negative aspects need to be considered so that it can always be accepted by the target reader. Because the assessment of translation is an integral part in the context of translation research, this study aims to determine the acceptance of English to Indonesian translations on Google Translate and more specifically to translations that use the reduced clause. In this study, researchers used Guardian News to be translated using Google Translation from English to Indonesian. In deciding the data's acceptability, the Translation Acceptability Assessment Instrument was initiated by Nababan et al. (2012) was used. The results of this study indicate that Most of the reduced clauses translated using Google Translate are considered acceptable in line with the qualitative parameter. However, there are still some of the data which are considered as less acceptable and not acceptable according to the qualitative parameter.